Autonomic Control of Measurement Data Integrity in Telemedicine Systems - Andrzej WALCZAK; Piotr BACZYK (Communications of International Proceedings, 2021)
This paper focuses on specific aspects of telemedicine systems relied upon for simultaneous measurement of electrocardiogram ECG and impedance cardiogram ICG signals. Using such systems, patients suffering from heart diseases measure their hemodynamic parameters on their own, without any external supervision, over a relatively long period of time, while the measuring device is turned on and off at irregular intervals. The data measured are transmitted to an external, IT-based diagnostic system that is the only location at which security checks may be performed. Protection offered by the user’s login and password is not sufficient to ensure data integrity and consistency of the measurement procedure described above.  Data integrity must be verified in order to ensure a sufficient degree of certainty and security of the diagnosis. Such verification should be performed by an autonomous, internal  system. Biometric verification of a fusion of cardiac signals is performed to ensure the integrity of data transmitted. Due to the potential variations in signal occurring over relatively long measurement periods, common biometry algorithms need to be modified, as no static biometric pattern is available in such a scenario. Signal fusion, serving as a source of biometric data, is another of the new approaches presented in our proposal.
Keywords: Impedance Cardiography; Biometrics; Telemedicine